Nocturnal hypoxia and arrhythmias in patients with impaired left ventricular function. Issue 10 (October 1992) - Cripps, T; Rocker, G; Stradling, J
Abstract : Objectives —To document the incidence of hypoxic episodes in a series of patients with impaired left ventricular function, and to correlate the occurrence of hypoxia with severity of arrhythmia. Patients —34 patients with breathlessness and clinical evidence of left ventricular dysfunction. Main outcome measures —Simultaneous overnight finger oximetry and electrocardiographic monitoring. Results —High grade arrhythmias (Lown grade >III) occurred in 20/34 (59%) of patients, and frequent dips in oxygen saturation were noticed (mean dip frequency 4·8/h, range 0·1–20·0). 20/34 (59%) of patients had episodic hypoxaemia, including 13/34 (38%) with a classical Cheyne Stokes pattern. There was a correlation between dip frequency and the presence of high grade arrhythmias (those with high grade arrhythmia had mean (SD) 6·7 (5·5) dips/h ν 2·2 (3·4) in those without, p < 0·01); there was also a correlation between the presence of arrhythmias and episodic hypoxaemia (episodic hypoxaemia in those with high grade arrhythmias occurred in 17/20 (85%) ν 3/14 (21%) of those without arrhythmias, p < 0·002). There was no correlation between the presence of high grade arrhythmias or dip frequency and the extent of left ventricular impairment, which was present in all patients (mean (SD) ejection fraction 26% (13%)). Conclusion —Noticeable abnormalities of nocturnal oxygen saturation occur in patients with impaired left ventricular function, and these are associated with high grade arrhythmias. Interventions that limit desaturation may have valuable anti-arrhythmic effects.